Hubungan Peran Teman Sebaya Dan Pola Asuh Orang Tua Terhadap Perilaku Berpacaran Pada Remaja Di SMP Negeri 129 Jakarta - Rifah Miladdina (2021)
The phenomenon of unhealthy dating behavior currently occurs in Indonesia, especially in early adolescence. Dating is a behavior that is carried out because there is a sense of attraction to other people and as a hope to get into married life. During early adolescence, dating behavior is influenced by several factors, such as the role of peers and parenting styles. The role of peers is individuals who have the same maturity and age level. Parenting is a way that parents do in guiding and supervising the behavior of children. This study was conducted to determine the relationship between the role of peers and parenting styles on dating behavior in adolescents at SMPN 129 Jakarta in 2021. The sample in this study was 236 students of SMPN 129 Jakarta. The sample used was stratified random sampling. The method used to determine the relationship between variables is the chi square test. The results of this study that there is a relationship between the role of peers on dating behavior with a value of p = 0.000 and for the parenting style variable, namely that there is a relationship between parenting patterns and dating behavior with a value of p = 0.000. The author recommends to conduct health education about promiscuity.